Accommodation and Binocular Vision in Children with Myopic Anisometropia - Chu-chu Zhuang; Ling Zhang; Shan-shan Pan; Yi-ning Wang; Jian-xin Guo (Journal of Ophthalmology)
Purpose. To assess the differences in accommodation and binocular vision in children with myopic anisometropia and determine the correlation with anisometropia. Method. A total of 110 patients with myopia aged 8–15 years were recruited from June 2021 to February 2022 from the Affiliated Hospital of Xuzhou Medical University. Based on the interocular differences of spherical equivalent refraction, patients were divided into the isometropia (35 children), low anisometropia (LA group, 42 children), and high anisometropia (HA group, 33 children). The variables assessed were refraction, heterophoria, amplitude of accommodation (AMP), accommodative response (AR), gradient AC/A, positive and negative relative accommodation (PRA/NRA), and near stereopsis in the three groups. Pearson’s correlation coefficient tests were used to investigate the possible association between each parameter and interocular differences (IODs). Results. Among 110 subjects, there were 49 males and 61 females with a mean age of 11.39 ± 2.28 years. Compared with those in the isometropia group, AMP was lower and near stereopsis was higher in the LA group, and the distance and near heterophoria, PRA, AR, and near stereopsis were higher, and PRA, AMP, and gradient AC/A were lower in the HA group (all P<0.05). Compared with those in the LA group, the near stereopsis, AR, and the near stereopsis were higher in the HA group, and the gradient AC/A was lower (all P<0.05). However, no significant differences existed in the negative relative accommodation (P>0.05). The distance and near heterophoria, AR, AMP, and near stereopsis were observed to be correlated with IODs, respectively (r = −0.259, p=0.006; r = −0.201, p=0.036; r = 0.306, p=0.001; r = −0.315, p=0.001; r = 0.535, p<0.001). Conclusion. Our results suggested that with the increase of anisometropia, distance and near heterophoria, AR, AMP, and near stereopsis had a tendency to get worse in children with myopic anisometropia.